2018
DOI: 10.1161/strokeaha.118.022133
|View full text |Cite
|
Sign up to set email alerts
|

Increased Blood Pressure Variability Contributes to Worse Outcome After Intracerebral Hemorrhage

Abstract: Background and Purpose- Increased systolic blood pressure variability (BPV) is associated with worse outcome after acute ischemic stroke and may also have a negative impact after intracerebral hemorrhage. We sought to determine whether increased BPV was detrimental in the ATACH-2 (Antihypertensive Treatment of Acute Cerebral Hemorrhage II) trial. Methods- The primary outcome of our study was a 3-month follow-up modified Rankin Scale of 3 to 6, and the secondary outcome was a utility-weighted modified Rankin Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…BPV is primarily divided into the three following categories: long-term (days to months), short-term (minutes to hours), and very shortterm (beat-to-beat) BPV (Parati et al, 2013). Most previous studies in patients with ICH have focused on the first two types of BPV and have reported that an increased BPV during both acute and subacute stages was independently associated with worse functional outcomes at 3 months (Manning et al, 2014;Tanaka et al, 2014;Lattanzi et al, 2015;Chung et al, 2018;de Havenon et al, 2018;Meeks et al, 2019). Tanaka et al and Rodriguez-Luna et al further revealed that SBPV was correlated with early neurological deterioration (Rodriguez-Luna et al, 2013;Tanaka et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPV is primarily divided into the three following categories: long-term (days to months), short-term (minutes to hours), and very shortterm (beat-to-beat) BPV (Parati et al, 2013). Most previous studies in patients with ICH have focused on the first two types of BPV and have reported that an increased BPV during both acute and subacute stages was independently associated with worse functional outcomes at 3 months (Manning et al, 2014;Tanaka et al, 2014;Lattanzi et al, 2015;Chung et al, 2018;de Havenon et al, 2018;Meeks et al, 2019). Tanaka et al and Rodriguez-Luna et al further revealed that SBPV was correlated with early neurological deterioration (Rodriguez-Luna et al, 2013;Tanaka et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis of five randomized, controlled, single/doubleblinded, parallel trials found no differences between aggressive and conservative BP-lowering strategies in the incidence rates of 3-months mortality and early neurological deterioration (Lattanzi et al, 2017). Post hoc analyses of the Field Administration of Stroke Therapy-Magnesium trial, Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial, and Antihypertensive Treatment of Acute Cerebral Hemorrhage II trial showed that increased BP variability (BPV) was associated with a poor functional outcome (Manning et al, 2014;Chung et al, 2018;de Havenon et al, 2018). This indicated that, in addition to the absolute BP level, BPV might also be a significant risk factor for worse outcomes after ICH.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 53 studies were retrieved for further full-text evaluations, and 46 studies were excluded due to the following reasons: patients with ischemic stroke (n = 27), retrospective design (n = 16), and review or meta-analysis (n = 3). After detailed evaluations, seven prospective studies were selected for the final quantitative metaanalysis (30)(31)(32)(33)(34)(35)(36). No new eligible study was detected by manually searching the reference lists of retrieved studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…A post hoc analysis of the Antihypertensive Treatment of Acute Cerebral Hemorrhage II (ATACH2) trial evaluated 1000 patients with ICH presenting within 4.5 hours with a SBP greater than 180 mm Hg . The trial evaluated intensive BP lowering (110‐139 mm Hg) as compared to standard treatment (140‐180 mm Hg) and given a pre‐specified protocol of antihypertensive agents, including continuous infusion of nicardipine for the first 24 hours.…”
Section: Data Surrounding Blood Pressure Variabilitymentioning
confidence: 99%